The diagnostic value of colposcopy in the diagnosis of cervical cancer with reference to histopathological findings - Zohre Yousefi Roodsari; Nourieh Sharifi Sistani; Malihe Hasanzadeh Mofrad; Negar Morrovatdar; Elaheh Saeedi; Mahya Labafchi (Mashhad University of Medical Sciences, 2022)
Introduction: One of the most important causes of cancer death in women is cervical cancer. Early detection of precursors or early stage disease is possible using low-cost and available screening approaches, and this is associated with a reduction in patients' mortality. This study was performed with aim to compare colposcopic findings and histological findings in colposcopic cervical biopsy specimens.Methods: This cross-sectional study was performed in 2016-2017 on 200 patients referred to the gynecology and oncology clinic of Ghaem Hospital in Mashhad with colposcopic indications. These indications included abnormal Pop smear, post coital bleeding, abnormal appearance of cervix and vagina on examination, and existence of high-risk HPV virus in tests. If there was a history of abnormal Pap smear or biopsy due to suspected cervical lesions, the subjects were excluded from the study. Initially, the cause of colposcopy, Pap smear and HPV status were extracted using the information in the file. In the next stage, under the supervision of two gynecologists with oncology fellowship, colposcopy was performed and the findings during colposcopy were recorded. Finally, the data were analyzed with the pathological report. Data were analyzed by SPSS software (version 23).Results: Physician diagnosis at the end of colposcopy was abnormal in 162 patients (81.5%). As a result of colposcopic pathology, the results showed abnormal pathology in 120 patients (60%). The most common pathologies reported were CIN1 (87.4%), CIN2 (9.2%), and CIN3 (2.3%), respectively. There was a correlation between the colposcopic result and the pathological result in 21% of patients (n=42). The sensitivity of colposcopy compared to the pathological result was 89% and its specificity was 30%. The positive and negative predictive value of colposcopy was 65% and 64% compared to the pathological result.Conclusion: Colposcopy has an acceptable sensitivity in the diagnosis of cervical pathological lesions, but has a low specificity. Therefore, this screening / diagnostic test can be used in one of the multi-stage screening stages (after the initial screening with Pap smear) and if there are any abnormalities during the colposcopy, biopsy be performed.